Empirical evidence of AMT practices and sustainable environmental initiatives in malaysian automotive SMEs - Dawal, S. (2015)
This paper presents significant empirical evidence on the relationship between Advanced Manufacturing Technology (AMT) practices and sustainable environmental initiatives with the manufacturing capabilities of automotive SMEs in Malaysia. A cross-sectional survey is adopted in this study, which involves 83 Malaysian automotive SMEs. Two hypotheses are proposed in this study, i.e. Hypothesis 1: There are positive effects of AMT practices on the manufacturing capabilities of SMEs and Hypothesis 2: There are positive effects of sustainable environmental initiatives on the manufacturing capabilities of SMEs. The results obtained from the pairwise correlation analysis indicate that both AMT practices and sustainable environmental initiatives have positive effects on manufacturing capabilities, which support both hypotheses. In addition, it is found that 50 of the SMEs implement AMT for flexibility and cost reduction in the past five years. It is also found that more than 80 sustainable practices are adopted in most of the SMEs with the exception of Life Cycle Assessment. Based on the findings, there is a need to move forward into the hybrid approach, which will consider both AMT practices and environmental initiatives to ensure that SMEs remain competitive and become the world player in the automotive industry.